2021
DOI: 10.1002/ecs2.3366
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal impoundment alters patterns of tidal wetland plant diversity across spatial scales

Abstract: Understanding patterns of biodiversity is a key goal of ecology and is especially pressing in the current human-caused biodiversity crisis. In wetland ecosystems, human impacts are centered around hydrologic manipulation including the common practice of wetland diking and impoundment. Constraining how wetland management influences plant biodiversity patterns across spatial scales will provide information on how best to modify actions to preserve biodiversity and ecosystem function in managed wetlands. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 64 publications
2
7
0
Order By: Relevance
“…This finding might be due to the positive roles of rainfall frequency and amount increases in increasing soil moisture contents (Fig. 1 ) and community species richness 53 , resulting in significantly high AB amounts (Table 1 ) and, consequently, enhancing the uptake of soil NH 4 + -N. Ammonium N (NH 4 + -N) is the main N form absorbed by plants due to its high solubility in the soil, increasing the chlorophyll-a content of plants and playing a key role in the leaf functional traits, thus increasing the AB amounts 54 . In addition, it was shown that rainfall variability significantly affects plant communities and their growth characteristics, as well as species compositions and diversity 55 .…”
Section: Discussionmentioning
confidence: 91%
“…This finding might be due to the positive roles of rainfall frequency and amount increases in increasing soil moisture contents (Fig. 1 ) and community species richness 53 , resulting in significantly high AB amounts (Table 1 ) and, consequently, enhancing the uptake of soil NH 4 + -N. Ammonium N (NH 4 + -N) is the main N form absorbed by plants due to its high solubility in the soil, increasing the chlorophyll-a content of plants and playing a key role in the leaf functional traits, thus increasing the AB amounts 54 . In addition, it was shown that rainfall variability significantly affects plant communities and their growth characteristics, as well as species compositions and diversity 55 .…”
Section: Discussionmentioning
confidence: 91%
“…The mosaic of wetlands and habitat types in Suisun Marsh, each with varying water management type (actively managed and tidal) and plant communities, provides a diversity of unique habitat patches that SMHM may select. In addition, the brackish water of Suisun Marsh promotes greater vegetation diversity than other portions of the SMHM geographic range (Jones et al., 2021). Most wetlands in the San Francisco Estuary outside Suisun Marsh where SMHM are found are oligohaline marshes and primarily composed of pickleweed ( Salicornia pacifica ; Padgett‐Flohr & Isakson, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Impacts from disturbances and changes in diversity drivers have also been shown to be scale dependent (Graham et al, 1990;Chaneton and Facelli, 1991;Bernhardt-Römermann et al, 2015). In managed tidal wetlands, plant diversity at local versus landscape scales was dependent on variables such as salinity gradients and water management (Jones et al, 2021). Differences in species rank and relative abundance across temporal and spatial scales can result from changes in community diversity and response to the environment (Jones et al, 2017;Avolio et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Vegetation patterns are important indicators of ecosystem transformations from anthropogenic stressors such as land-use change (Tasser and Tappeiner 2002), non-native species invasion (Sundaram and Hiremath, 2012), and water diversion (Elmore et al, 2003). For example, land area may change when freshwater diversion or reconnections occurs (White et al, 2023) and plant communities may change with diking of low tidal lands (Mora and Burdick, 2013) or seasonal impoundment of tidal marshes (Jones et al, 2021). Large scale ecosystem transformations have been documented over the last century primarily due to human disturbance, including modification to hydrologic conditions (Busch et al, 1998).…”
Section: Introductionmentioning
confidence: 99%